Glycosylation in Cervical Cancer: New Insights and Clinical Implications - Xu, Zhiwei; Zhang, Yaqin; Ocansey, Dickson K. W.; Wang, Bo; Mao, Fei (Frontiers in Oncology, 2021)
Cervical cancer has become the most frequent female malignancy and presents as a general health challenge in many countries undergoing economic development. Various human papillomaviruses (HPV) types have appeared as one of the most critically identifiable causes of widespread cervical cancers. Conventional cervical cytological inspection has limitations of variable sensitivity according to cervical cytology. Glycobiology has been fundamental in related exploration in various gynecologic and reproductive fields and has contributed to our understanding of cervical cancer. It is associated with altered expression of N-linked glycan as well as abnormal expression of terminal glycan structures. The analytical approaches available to determine serum and tissue glycosylation, as well as potential underlying molecular mechanisms involved in the cellular glycosylation alterations, are monitored. Moreover, cellular glycosylation influences various aspects of cervical cancer biology, ranging from cell surface expressions, cell-cell adhesion, cancer signaling, cancer diagnosis, and management. In general, discoveries in glycan profiling make it technically reproducible and affordable to perform serum glycoproteomic analyses and build on previous work exploring an expanded variety of glycosylation markers in the majority of cervical cancer patients.